2003
DOI: 10.1017/s0033291703008213
|View full text |Cite
|
Sign up to set email alerts
|

Older adults and withdrawal from benzodiazepine hypnotics in general practice: effects on cognitive function, sleep, mood and quality of life

Abstract: Background. Older adults are the main recipients of repeat prescriptions for benzodiazepine (BZD) hypnotics. BZDs can impair cognitive function and may not aid sleep when taken continuously for years. This study therefore aimed to determine if withdrawing from BZDs leads to changes in patients' cognitive function, quality of life, mood and sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(112 citation statements)
references
References 38 publications
(42 reference statements)
5
105
1
1
Order By: Relevance
“…These range from 25% at 12 months for those with complicated dependence 15 to 80% for older adults in general practice. 16 Abrupt cessation of benzodiazepines after a period of 1-6 months of use can cause life-threatening seizures so the dose should be gradually reduced.…”
Section: Discontinuation With the Aim Of Abstinencementioning
confidence: 99%
“…These range from 25% at 12 months for those with complicated dependence 15 to 80% for older adults in general practice. 16 Abrupt cessation of benzodiazepines after a period of 1-6 months of use can cause life-threatening seizures so the dose should be gradually reduced.…”
Section: Discontinuation With the Aim Of Abstinencementioning
confidence: 99%
“…Interestingly, randomised controlled trials have shown that withdrawal from benzodiazepines give significant better psychomotoric function compared to the control group remaining on benzodiazepines [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Only 1 RCT made wanting to discontinue a specific participant inclusion criterion [20], but 8 more commented on the issue (e.g., it is “difficult” to recruit treatment-responding participants “who are willing to be potentially randomly assigned to placebo” [21]; “participants were motivated ... and willing to discontinue their hypnotic medication” [22]). Similarly, 12 of 80 trials commented on environmental influences on discontinuation such as “caregiver distress and shortness of available staff time” [23]), but only 2 (discontinuing APs from residents with intellectual disability) assessed such variables, reaching opposite conclusions: “[C]hanges in environmental circumstances were of no influence on completion or non-completion of ... discontinuation” [24] and “[D]ifferences [between successfully or unsuccessfully drug-reduced participants] were apparent ... mainly in staff and environmental characteristics” [25].…”
Section: Resultsmentioning
confidence: 99%